EBF recommendation for stability testing of anti-drug antibodies; lessons learned from anti-vaccine antibody stability studies. (May 2014) - Pihl, Susanne; Michaut, Lydia; Hendriks, Jenny; Loebbert, Ralf; Ryding, Janka; Nemansky, Martin; Vermet, Laurent; Companjen, Arjen
Long- and short-term stability testing of the analyte is one of the key parameters in bioanalytical method validation in support of pharmacokinetics. However, for immunogenicity testing, the scientific rationale for long- and short-term stability testing on quality control samples most often spiked with polyclonal antibody raised in a different species should be questioned. Therefore, the European Bioanalysis Forum (EBF) formed a Topic Team to discuss the scientific rationale for stability testing of anti-drug antibodies (ADAs). A review of EBF member companies' experience on ADA stability and on anti-vaccine antibodies from vaccine projects was the basis of this discussion. EBF recommends to perform short-term stability testing of the positive control, but not to perform long-term stability testing of ADAs in nonclinical and clinical studies.